2014
DOI: 10.1093/nar/gku269
|View full text |Cite
|
Sign up to set email alerts
|

DNA–protein π-interactions in nature: abundance, structure, composition and strength of contacts between aromatic amino acids and DNA nucleobases or deoxyribose sugar

Abstract: Four hundred twenty-eight high-resolution DNA–protein complexes were chosen for a bioinformatics study. Although 164 crystal structures (38% of those searched) contained no interactions, 574 discrete π–contacts between the aromatic amino acids and the DNA nucleobases or deoxyribose were identified using strict criteria, including visual inspection. The abundance and structure of the interactions were determined by unequivocally classifying the contacts as either π–π stacking, π–π T-shaped or sugar–π contacts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
178
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(183 citation statements)
references
References 127 publications
4
178
0
1
Order By: Relevance
“…S2; Wilson et al 2014Wilson et al , 2015. In this previous study, 1765 contacts were identified in 672 X-ray crystal structures published prior to January 2, 2014 with a resolution better than 2.0 Å.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…S2; Wilson et al 2014Wilson et al , 2015. In this previous study, 1765 contacts were identified in 672 X-ray crystal structures published prior to January 2, 2014 with a resolution better than 2.0 Å.…”
Section: Introductionmentioning
confidence: 95%
“…Due to the importance of nucleic acid-protein interactions, a number of studies have analyzed experimental Xray crystal structures to understand the types of atomic level interactions between DNA Luscombe and Thornton 2002;Gromiha et al 2004aGromiha et al ,b, 2005Mao et al 2004;Lejeune et al 2005;Prabakaran et al 2006;Baker and Grant 2007;Sathyapriya et al 2008;Wilson et al 2014Wilson et al , 2015 or RNA (Allers and Shamoo 2001;Jones et al 2001;Treger and Westhof 2001;Cheng et al 2003;Jeong et al 2003;Lejeune et al 2005;Morozova et al 2006;Baker and Grant 2007;Ellis et al 2007;Bahadur et al 2008;Barik et al 2015) nucleotides and amino acids that govern nucleic acid recognition and binding. These studies have determined that nucleic acid-protein contacts span hydrogen bonding (direct or water mediated), ionic (salt-bridge or phosphate backbone), van der Waals, and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations